Paraquat poisoning: a case report - Paul, Prannoy; Biju, Asha (International Journal of Advances in Medicine, 2020)
Paraquat (1, r-dimethyl-4, 4’-bipyridium dichloride) is a commonly used herbicide in Asia. In spite of its wide availability, poisoning due to this herbicide is uncommon. An ingested dose of more than 10 ml is known to cause irreversible lung injury. Due to lack of any specific diagnostic test or specific clinical signs, diagnosis is often difficult without identifying the compound from history. Poisoning with high doses is associated with poor prognosis. As there is no specific antidote, treatment is aggressive decontamination and supportive management. However, in high doses, cases are often fatal.